The effectiveness of hot and cold executive function training on internalized and externalized behaviors in hyperactive children - Attari, Zahra; Jafar Tabatabaee, Toktam Sadat; Jafar Tabatabaee, Samaneh Sadat; Nasseri, Saeed (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The aim of this study was to determine the effectiveness of hot and cold executive function training on internalized and externalized behaviors in hyperactive children. Methods: The present study was a quasi-experimental study with a pretest-posttest research design with a control group along with a follow-up period. The statistical population of the study included all elementary school students (first, second and third grade) with attention deficit / hyperactivity disorder in the academic year 2019-20 who referred to education counseling centers in Tehran, among which A total of 30 inactive children were selected using convenience sampling method and randomly assigned to experimental and control groups (n=15). Data were obtained using the Connors Parent Questionnaire and the Achenbach Child Behavior Inventory - Parental Prescription (Achenbach, 1991). The hot and cold executive functions training program of Aziziyan et al. (2016) was performed on the experimental group in 10 sessions of 90 minutes, but the control group remained on the waiting list. Repeated measure analysis of variance and Spss.22 software were used to analyze the data. Results: The results showed that the training of hot and cold executive functions on internalized (F=3.59, p=0.036) and externalized (F=9.24, p<0.001) behaviors was hyperactive in children. Conclusion: It can be concluded that hot and cold executive functions were effective on internalizing and externalizing behaviors in hyperactive children and this method can be used to improve the problems of hyperactive children.